High Risk of Acquired Immune Deficiency Syndrome (AIDS) and of AIDS Related Complex (ARC) in Hemophiliacs Seropositive for more than 5 Years - Stain, C; Pabinger-Fasching, I; Guggenberger, K; Köller, U; Stain, M; Hartl, H; Heinz, F; Mayerhofer, S; Kyrle, P A; Lechner, K; Korninger, C (Thrombosis and Haemostasis, 1989)
A group of 90 hemophiliacs who had been regularly treated with non virus-inactivated factor VIII or IX concentrates were studied in 1983. At that time 50 patients were HIV-1-antibody positive, 6 additional seroconversions occurred until 1985. 26 of the 50 patients seropositive in 1983 are currently asymptomatic. 4 patients have developed the lymphadenopathy syndroffie, 9 patients AIDS and 11 patients ARC (CDC IV C 2). 6/9 cases of AIDS and 10/11 cases of ARC have occurred only after 1985. Patients, who subsequently became symptomatic, had significantly higher IgG levels in 1983, otherwise no predictive laboratory tests were identified. Patients with T4 counts above 500/μl became symptomatic later, but after 5 years the indicence of AIDS was comparable in patients with original T4 counts of more than or below 500/μl.
Keywords: Hemophilia; Clotting factor concentrates; Acquired immune deficiency syndrome; Human immune deficiency virus